2021
DOI: 10.3389/fphys.2021.571826
|View full text |Cite
|
Sign up to set email alerts
|

Crowdsourced Identification of Potential Target Genes for CTV Induced Gene Silencing for Controlling the Citrus Greening Vector Diaphorina citri

Abstract: Citrus Greening or Huanglongbing (HLB) is a disease of citrus, causing high reduction in citrus production and is transmitted by the Asian citrus psyllid Diaphorina citri Kuwayama vectoring a phloem-limited bacterium Candidatus Liberibacter sp. We report research results using crowdsourcing challenge strategy identifying potential gene targets in D. citri to control the insect using RNA interference (RNAi). From 63 submitted sequences, 43 were selected and tested by feeding them to D. citri using artificial di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 86 publications
(124 reference statements)
1
4
0
Order By: Relevance
“…DNA bands of 1160 bp were found in columns 4, 11, and 12, while the other columns were negative. This is in line with the statement of [3], that not all leaves on twigs show symptoms of attack Positive CVPD contains CLa bacteria. It can happen that the upper leaves are positive for bacteria while the lower leaves are negative [3], also stated that this finding shows that there is no need for the presence of a pathogen on the plant leaves to cause disease symptoms or in other words, pathogens that are on the leaves of other plants can cause symptoms to appear on the leaves next to them or above and below them.…”
Section: Icopodsupporting
confidence: 91%
See 3 more Smart Citations
“…DNA bands of 1160 bp were found in columns 4, 11, and 12, while the other columns were negative. This is in line with the statement of [3], that not all leaves on twigs show symptoms of attack Positive CVPD contains CLa bacteria. It can happen that the upper leaves are positive for bacteria while the lower leaves are negative [3], also stated that this finding shows that there is no need for the presence of a pathogen on the plant leaves to cause disease symptoms or in other words, pathogens that are on the leaves of other plants can cause symptoms to appear on the leaves next to them or above and below them.…”
Section: Icopodsupporting
confidence: 91%
“…CVPD causes damage to the vessels of plant tissues, especially in the leaves so the photosynthetic process in plants can be hampered even to the point where photosynthesis blocks occur (photosynthesis cannot occur) due to CVPD which damages plant vascular cells [19]. In this study, the Diaphoryna citri vector was not found either at the rootstock source location or in the nursery due to several factors such as the absence of host plants other than citrus which are favored by the vector, such as kemuning which does not grow around nurseries or mother gardens and has not yet entered the bud formation new period [3] reported that Diaphorina citri tends to prefer yellowing because it is a plant that is resistant to pruning and has young buds continuously. The existence of other host plants around citrus plantations needs to be considered because they can become a reservoir for Diaphorina citri [10].…”
Section: Cvpd Diseasementioning
confidence: 66%
See 2 more Smart Citations
“…Other approaches not requiring plant modification have been developed. Plants infected with modified viruses have been widely used for screening potential RNAi target genes [ 244 , 245 , 246 , 247 ], and similar viruses may also confer protection to plants against fungi and nematodes [ 248 , 249 ]. The virus acts as a dsRNA factory during its replication in the plant.…”
Section: Sources Of Dsrnas With Insecticidal Effectmentioning
confidence: 99%